Islamic Teachings on Love of Homeland According to the Qur'an - Faruqi, Nasrulloh Al; Suharyat, Yayat (MultiTech Publisher, 2023)
Love of the homeland is a very subtle and deep feeling in the human heart with which love of the homeland arises from true faith so as to cause the feeling to sacrifice for the glory of the motherland. The study of the concept of this discussion aims to foster a deep feeling of love for the homeland for a Muslim because it has been taught in the Qur'an. This research uses literature method with qualitative approach. The results showed that Islam has taught its adherents to love their homeland with the sources of evidence contained in the Qur'an. It can be said that Islam is a teaching that cares for the homeland so that its adherents must sacrifice and care for their homeland.